Thromboembolic and haemorrhagic complications after heart valve surgery – we are not allowed to forget about this problem - Trzeciak, Przemysław; Poloński, Lech; Zembala, Marian (Przewodnik Lekarza/Guide for GPs, 2007)
Patients after heart valve surgery need systematic medical care due to the danger of haemorrhagic and thromboembolic complications. The case report of a 58-year-old man after artificial mitral valve replacement is presented. Nineteen months after surgery he was admitted to hospital due to ischaemic stroke. The necessity to distinguish from a group of patients with mechanical heart valve prosthesis those at high risk of haemorrhagic and thromboembolic complications is emphasized. The interactions of oral anticoagulants with drugs and food have been presented. The standards of cessation of anticoagulant treatment before surgery are shown. The duty of general practitioners, cardiologists and cardiac surgeons is to create an outpatient care system to protect patients from thromboembolic complications.